Pendampingan Belajar Ilmu Tajwid Terhadap Anak Usia Sekolah Dasar Dusun Krajan Desa Karangpatihan Kecamatan Pulung Kabupaten Ponorogo - Santriana Rohmatin; Ibnu Muchlis (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article will explain the lack of elementary school-age children who have the ability to be able to read the Qur'an properly according to the rules of tajwid. The purpose of this service is to provide free learning assistance to elementary school-age children in Krajan Hamlet, Karangpatihan Village. The service method used is Asset Based Community Development (ABCD). The result of this research is to bring up elementary school-age children who are able to understand the science of recitation. So that in the future the young people of Dusun Krajan, Karangpatihan Village, in particular, will be able to read the Al-Qur'an properly and correctly.